TL 18099 - Short-term changes after corticosteroid injections into the normal tendons of rabbits: a controlled randomized study - Godoy-Santos, Alexandre Leme; Innocenti Dinhane, Kandir Genesio; Todorovic Fabro, Alexandre; Moretto, Maria Regina; Depra, Igor; Bonetti Yoshida, Winston (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Corticosteroid injections in or around tendons for the treatment of athletic injuries are a common practice among orthopedic surgeons and are apparently efficacious in the short term, although controversies persist related to local complications. Objective: This study evaluated short-term (48 hours) biomechanical, biochemical, and histological alterations after a single injection of betamethasone into the normal tendons of rabbits. Methods: A total of 72 New Zealand White rabbits were randomly divided into 2 groups: the test group - in which 36 animals underwent 1 intratendinous injection of betamethasone (1.4 mg / 0.2 mL) in the right calcaneal tendon; the control group - in which the right calcaneal tendon of 36 animals was injected with saline (placebo control group) and the left calcaneal tendon was left untreated for normal standards (normal control). Forty-eight hours later, the animals were euthanized and the tendons harvested. Metalloproteinase (MMP1 and MMP2) and interleukin (IL1 and IL6) expression levels, biomechanical resistance (load 3 elongation parameters), and histomorphometry (hematoxylin and eosin and picrosirius red stains for collagen fibers, tenocytes, and inflammatory cells) were analyzed in the tendons. Results: The test group showed a significant reduction in MMP2 expression compared with the control groups (P = .027). Regarding the other parameters, there were no additional significant differences between the groups. Conclusion: A single injection of corticosteroid into normal calcaneal tendons did not trigger acute local morphological, structural, or biomechanical injuries at 48 hours, but it did promote a significant decrease in MMP2 levels. Additional studies are needed with increased follow-up durations, various doses, and multiple injections and in tendinopathic models.